1991
DOI: 10.1038/350718a0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of telomerase by G-quartet DMA structures

Abstract: The ends or telomeres of the linear chromosomes of eukaryotes are composed of tandem repeats of short DNA sequences, one strand being rich in guanine (G strand) and the complementary strand in cytosine. Telomere synthesis involves the addition of telomeric repeats to the G strand by telomere terminal transferase (telomerase). Telomeric G-strand DNAs from a variety of organisms adopt compact structures, the most stable of which is explained by the formation of G-quartets. Here we investigate the capacity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
854
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,079 publications
(870 citation statements)
references
References 19 publications
14
854
1
1
Order By: Relevance
“…19 It has been shown that formation of G-quadruplexes by the telomeric G-rich strand inhibits the activity of telomerase. 20 This inhibition is most likely due to the trapping the 3′-end guanines within the G-tetrad core. Use of small molecules for stabilizing telomeric G-quadruplex has been proposed as one of the anti-telomerase strategies for the development of anticancer drugs.…”
Section: Biological and Pharmacological Implicationsmentioning
confidence: 99%
“…19 It has been shown that formation of G-quadruplexes by the telomeric G-rich strand inhibits the activity of telomerase. 20 This inhibition is most likely due to the trapping the 3′-end guanines within the G-tetrad core. Use of small molecules for stabilizing telomeric G-quadruplex has been proposed as one of the anti-telomerase strategies for the development of anticancer drugs.…”
Section: Biological and Pharmacological Implicationsmentioning
confidence: 99%
“…The 3' terminal region of the G-rich strand of human telomeres is single-stranded and may adopt a G-quadruplex conformation [19]. This structure has been shown to directly inhibit telom-erase elongation in vitro [20]. Telomeres protect chromosomal ends from fusion events and provide a means for complete replication of the chromosome.…”
Section: Fig 1 (A) Formulae Of Cryptolepine (5-methyl Indolo[23b]-mentioning
confidence: 99%
“…The non-folded, single-stranded form of the primer is required for optimal telomerase activity and qua-druplex formation has been shown to directly inhibit telomerase elongation in vitro [20]. A growing number of small molecules have been discovered to inhibit telomerase activ ity by inducing and/or stabilizing G-quartet structure [45,46], including l0H-indolo [3,2-b] quinoline derivatives [47].…”
Section: Telomerase Inhibitionmentioning
confidence: 99%
“…G-quadruplex structures have been implicated in the elongation of telomeric DNA by telomerase (Han and Hurley, 2000). The nonfolding single-stranded telomere overhang is required for an optimal telomerase reaction, and G-quadruplex formation has been shown to inhibit telomerase elongation in vitro (Zahler et al, 1991). Agents that stabilize G-quadruplexes have the potential to interfere with telomere replication by blocking the elongation step catalysed by telomerase, and thus are very attractive targets for drug design (Mergny and Helene, 1998).…”
Section: Introductionmentioning
confidence: 99%